Corporate Strategies and Financial Performance among Foreign Commercial Banks in Bujumbura, Burundi - Shingiro, Jean Oxas; Awolusi, Olawumi Dele (Journal of Economics and Behavioral Studies, 2023)
This study investigated the relationship between corporate strategies and financial performance among foreign commercial banks in Burundi. The study used cross-sectional descriptive research design using a quantitative approach. The target population was 219 employees including technical staff and management. A sample size of 142 respondents was determined and simple random sampling was used to select the respondents. The questionnaire was used as the main data collection instrument and data was analyzed using linear and multiple regression analysis. The study revealed that corporate strategy significantly affects the financial performance of foreign commercial banks in Bujumbura (Adjusted R2=0.281, p=0.000). In addition, it was found that competitive strategy significantly affects the financial performance of foreign commercial banks in Bujumbura (Adjusted R2=0.147, p=0.000). Similarly, the study revealed that operational strategy significantly affects the financial performance of foreign commercial banks in Bujumbura (Adjusted R2=0.229, p=0.000). The study concluded that corporate strategies significantly affect financial performance. The study made the following recommendations: management of foreign commercial banks should employ the use of a total quality management system, should make use of a customer relationship management system, should employ advanced and constant methods of market research, and continuously develop new processes of delivering quality services to their customers.